Technology and policy review for homeland security. - Kun, L. (IEEE Engineering in medicine and biology magazine)
This article looks at information, and information technology in general, to show how certain aspects are so critical to all the homeland security mission areas that, on their own, they may determine whether the outcome is a failure or a success. From preparing for to preventing a threat and from managing, responding, and recovering from an attack, the timely delivery of information has become the centerpiece to achieving success. The existing interrelations among all critical infrastructures (that currently support our way of life) are such that only with a carefully planned and executed systems-approach, both for technology and policy as well, we will be able to address homeland security effectively. Some current evolving new policies for homeland security and proposed legislation are briefly reviewed here as well because of their criticality. As we create and apply new tools, techniques, and devices to help solve our problems at hand, a set of new procedures will need to be instilled and followed, and new policies will supply the required direction and financial support needed to be enacted.